2011
DOI: 10.1364/oe.19.005993
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of high density through silicon vias with spectral reflectometry

Abstract: Measurement and control is an important step for production-worthy through silicon vias etch. We demonstrate the use and enhancement of an existing wafer metrology tool, spectral reflectometer by implementing novel theoretical model and measurement algorithm for high density through-silicon via (HDTSV) inspection. It is capable of measuring depth and depth variations of array vias by Discrete Fourier Transform (DFT) analysis in one shot measurement. Surface roughness of via bottom can also be extracted by scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…It should be noted that the single obtained frequency indicates that the depth variations among the vias within the illumination area are smaller than the resolution limit of the depth variation of 0.36 μm, as we determined in Ref. 17. There is a slight broadening on the right side of the main peak, which reveals there might be vias slightly deeper than 28.51 μm within the illumination area.…”
Section: Resultsmentioning
confidence: 45%
See 1 more Smart Citation
“…It should be noted that the single obtained frequency indicates that the depth variations among the vias within the illumination area are smaller than the resolution limit of the depth variation of 0.36 μm, as we determined in Ref. 17. There is a slight broadening on the right side of the main peak, which reveals there might be vias slightly deeper than 28.51 μm within the illumination area.…”
Section: Resultsmentioning
confidence: 45%
“…14,15 In our previous studies, we demonstrated the use and enhancement of this existing wafer metrology tool by implementing a novel theoretical model and measurement algorithm for HAR TSV measurements. 16,17 TSV manufacturing process with high etch rate stages combined with efficient passivation or deposition steps have achieved nearly anisotropic shapes, with high etch rates of 5 μm/min or greater. 18,19 Good etch depth uniformity and shape requirements for 3-D integration are necessary in a high-volume manufacturing process.…”
Section: Introductionmentioning
confidence: 99%
“…Optical interferometry and reflectometry are the main nondestructive metrological methods for this purpose [11][12][13] but their use is limited for smaller diameter TSVs due to the requirement of obtaining a measurable signal of reflected light from the bottom of the TSV. The nondestructive 3D metrology of deep-etched structures with an aspect ratio of more than 10 and patterns with lateral dimensions in the range below 5 lm remains a challenge.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…The measurement of depths and diameters of TSVs is very important for the monitoring process during fabrication. Some researchers have tried to measure the depths and diameters of TSVs using scanning electron microscopes [1], infrared (IR) microscopes [2][3][4], diffraction phenomena [5], laser interferometry [6,7], reflectometry [8,9] and white-light interferometry [10,11]. There has been, however, very little research on the critical dimension of the bottom part of the TSV, that is, the bottom CD.…”
Section: Introductionmentioning
confidence: 99%